Peripheral Intravenous Catheter Securement in Infants in the Neonatal Intensive Care Unit - Wagan, Kniessl (My University, 2014)
Objectives: The quality of securement directly impacts the functionality, duration of patency and likelihood of a complication for a given peripheral intravenous catheter. The objective of the study was to determine which method of peripheral intravenous catheter securement, StatLock or Tegabear dressing was more effective by comparing duration of catheter patency and complication rates. Study Design & Method: A quasi-experimental study using the Model for Improvement was conducted in a neonatal intensive care unit of a tertiary care hospital. Infants requiring insertion of a peripheral intravenous catheter for parenteral nutrition or administration of medications were eligible to participate. The study was conducted over a 4-month period and was divided into two phases, with each phase lasting two months. Results: A total of 363 peripheral intravenous catheters were inserted in 175 infants. There were 211 catheters secured with StatLock and 108 secured with Tegabear dressing. There were 42 catheters which were unable to use StatLock or Tegabear dressing and were secured with a combination of transparent dressing/ tape. There were two peripheral intravenous catheters inserted where the method of securement was not indicated. The groups were similar with regards to all demographic variables except postmenstrual age, where the Tegabear group consisted of a larger proportion of older infants (p=<0.001). There was no significant difference in the mean duration of catheter patency between the StatLock and Tegabear group (46.04 hours versus 45.33 hours respectively), p=0.84. Complication rates and reasons for catheter removal did not significantly differ between the two groups (p=0.78 and p=0.93 respectively). The proportion of catheters that used an arm board was significantly greater with the Tegabear dressing (23.8%) compared to 10.5% with StatLock (p=0.002). Twenty one percent (n=23/108) of the catheters secured with the Tegabear dressing required reinforcement with tape or transparent dressing whereas no catheters in the StatLock group needed to be reinforced (p<0.001). Conclusion: Catheter dwell time and complication rates did not differ significantly between StatLock and Tegabear dressing. However, when evaluating a new product, it is important to consider that there is often a learning curve that must be overcome. A larger study with a more rigorous design such as a randomized controlled trial is needed to validate or dispute the study findings. In the meantime, nurses must exercise individual and independent judgment when selecting a securement method most appropriate for their patient.
Peripheral Intravenous Catheter Securement in Infants
Keywords: peripheral intravenous catheter securement; infants; Neonatal Intensive Care Unit